2019
DOI: 10.1097/md.0000000000015934
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke rehabilitation

Abstract: The aim of this study was to examine predictors of discharge of hospitalized stroke patients to either an acute inpatient rehabilitation facility (IRF) or subacute skilled nursing facility (SNF). A retrospective cohort study was done in a large multicampus urban academic medical center of individuals hospitalized for stroke between January 1, 2015 and December 31, 2015 and who were discharged to either an IRF (n = 84) or SNF (n = 59). A set of characteristics and scales were collected on each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 25 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Many of those who are discharged from hospital after a stroke have tenacious impairments, including weakness, balance difficulty, cognitive impairment, immobility, and dependency in activities of daily living ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of those who are discharged from hospital after a stroke have tenacious impairments, including weakness, balance difficulty, cognitive impairment, immobility, and dependency in activities of daily living ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of those who are discharged from hospital after a stroke have tenacious impairments, including weakness, balance difficulty, cognitive impairment, immobility, and dependency in activities of daily living (16,17). These severe physical, social, and psychological consequences can be devastating and coping with the outcome tends to be extremely difficult with an abundance of adjustments and variations in young adults' physical abilities, social integration, and family roles (3,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…33 Individuals in urban areas are having strokes at younger ages, and younger individuals are less likely to be recommended subacute rehabilitation compared with older adults with stroke, which demonstrates another reason why this association may persist. 34…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of clinical literature review, [19][20][21][22][23] several domains were identified by the authors to be pertinent to rehabilitation needs. These included: ► New functional dependency, indicated by an increased level of physical assistance required for mobility, personal care and/or the need for assistive equipment (such as a mobility aid).…”
Section: Design Developing a Proactive Rehabilitation Screening (Presmentioning
confidence: 99%